Sequential Bargaining as a Noncooperative Foundation for Walrasian Equilibrium - McLennan, Andrew; Sonnenschein, Hugo (Econometrica, 1991)
An allocation for an exchange economy with smooth preferences is shown to be Walrasian if there is a set of net trades that is closed under addition, contains the negations of net trades that would improve any agent's final bundle, and is such that each agent's final bundle is weakly preferred to the sum of the initial endowment and any allowed net trade. These conditions characterize the sets of net trades available in equilibria of market games in which randomly paired agents bargain repeatedly and imply that steady state equilibria are Walrasian. Copyright 1991 by The Econometric Society.